THE EFFECT OF ORGANIZATIONAL CULTURE AND WORK SATISAFACTION TOWARD OCB TROUGH MEDIATION OF ORGANIZATIONAL COMMITMENT - Dania, Rizki Firdausi Rachma (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to see the effect of organizational culture and job satisfaction in encouraging employees to do extra activities outside of workload. This research is focused on hotel X. The choice of place for this research is due to the advancement of the hospitality industry which directly increases competition between actors in this industry. As a service industry, hospitality relies on employees who are engaged in the service sector and meet directly with consumers. Therefore the respondents in this study were 108 employees who work to service customer. This research is processed by path analysis. From the results of the study, it is concluded that organizational culture affects the increase in OCB of hotel X employees directly or through mediation of organizational commitment. Meanwhile, job satisfaction does not affect the formation of OCB among respondents. However, if mediated by organizational commitment, job satisfaction can also increase the formation of OCB. Therefore, it is recommended for company X to improve organizational culture and increase job satisfaction so that employee commitment to the company can increase. Increasing of organizational commitment can stimulate employees to increase their willingness to do work outside the workload.